Targeting the programmed cell death 1 pathway in Hodgkin lymphoma: the place of nivolumab. (May 2017) - Gay, Nathan D.; Okada, Craig Y.; Chen, Andy I.; Scott, Emma C.
Nivolumab is a humanized immunoglobulin gamma-4 kappa anti-programmed cell death 1 monoclonal antibody that is currently approved in the treatment of several solid tumors and recently gained accelerated approval in classical Hodgkin lymphoma (cHL) that has relapsed or progressed following autologous hematopoietic stem-cell transplantation and post-transplantation brentuximab vedotin. The purpose of this article is to review the immunophysiologic basis, clinical efficacy, and toxicity of nivolumab in the treatment of cHL. In addition, we will review ongoing clinical trials and potential future directions of checkpoint inhibition in the treatment of cHL.